The all-girl filling station's last reunion [compact disc, unabridged] : a novel - Flagg, Fannie (Random House Audio, 2013)
"Spanning decades, generations, and America in the 1940s and today, The All-Girl Filling Station's Last Reunion is a fun-loving mystery about an Alabama woman today, and five women who in 1943 worked in a Phillips 66 gas station, during the WWII years. Like Fannie Flagg's classic Fried Green Tomatoes, this is a riveting, fun story of two families, set in present day America and during World War II, filled to the brim with Flagg's trademark funny voice and storytelling magic"--